Peningkatan Jiwa Kewirausahaan Siswa SD Utama 2 Tarakan Melalui Pembuatan Gelang oleh Mahasiswa UBT - Hidayat, Nurul; Rahmadina, Angieta; Kresti, Fransisca Estriani Novita; Aprisilawati, Meta; Hidayat, Muhammad Nur; Hanif, Raihan (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
The mini entrepreneurship socialization activity themed "Bracelet Making as an Initial Step into Entrepreneurship" was conducted at SDN 020 Tarakan, Jl. Sebengkok Pelayaran, as an implementation of managerial knowledge, particularly in the field of entrepreneurship. This activity aimed to cultivate entrepreneurial spirit among elementary school students by introducing them to simple production processes and basic selling practices. The methods used included interactive lectures to explain basic entrepreneurial concepts, bracelet-making demonstrations as a hands-on craft activity, and in-class sales simulations to train students in communication and confidence when offering products. The results showed that this approach was effective in increasing students’ enthusiasm, creativity, and self-confidence. The activity demonstrated that entrepreneurial education can be introduced at an early age through simple, contextual, and engaging methods.